Fenomena Bilingualisme dan Diglosia pada Masyarakat Tutur Keturunan Arab di Kampung Arab Kota Pamekasan - Kusumawati, Hesti; Adriana, Iswah; Romadhon, Sahrul (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Bilingualism is a common phenomenon in Indonesian society, where the majority of people use two or more languages. In Pamekasan, particularly among the Arab descendant community, Madurese, Indonesian, and Arabic are used according to their respective functions. This situation gives rise to various linguistic phenomena such as code-switching, code-mixing, and interference, occurring in both formal and informal contexts. This phenomenon is worth studying as it relates to bilingualism and diglossia. The aim of this study is to describe the level of bilingualism among the Arab descendant speech community in the Arab quarter of Pamekasan, as well as its relationship with diglossia and the factors that influence it. The research employed a qualitative descriptive method, with data consisting of words, phrases, clauses, and sentences from the daily speech of the community. The data sources were bilingual Arab descendants residing in the Arab quarter. Data collection techniques included non-participant observation and note-taking, and the analysis was conducted critically through identification, classification, interpretation, and description. The results show, first, that coordinate bilingualism is more dominant than subordinate or compound bilingualism. Second, the Arab descendant community in Pamekasan is bilingual but not diglossic. Third, factors influencing these linguistic phenomena include bilingualism itself, interlocutors, speech situations, prestige, and language acquisition. In conclusion, the Arab descendant community in Pamekasan demonstrates strong bilingual competence with a tendency toward coordinate bilingualism but without diglossia. This research contributes to the field of sociolinguistics, particularly in understanding the relationship between